2017
DOI: 10.1021/acs.analchem.7b00916
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Online Liquid Chromatography–Surface-Enhanced Raman Scattering (LC-SERS) of Methotrexate and its Major Metabolites

Abstract: The application of Raman spectroscopy as a detection method coupled with liquid chromatography (LC) has recently attracted considerable interest, although this has currently been limited to isocratic elution. The combination of LC with rapidly advancing Raman techniques, such as surfaceenhanced Raman scattering (SERS), allows for rapid separation, identification and quantification, leading to quantitative discrimination of closely eluting analytes. This study has demonstrated the utility of SERS in conjunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…[85,86]). More recently, an improved on-line LC-SERS system using reversed phase LC, where enhanced analyte separation was possible by programming the mobile phase during elution, showed that it was possible to target and quantitate methotrexate and its major metabolite 7-hydroxy methotrexate in urine from human patients suffering from rheumatoid arthritis [87].…”
Section: Multiplexed Quantification From Sers Of Mixturesmentioning
confidence: 99%
“…[85,86]). More recently, an improved on-line LC-SERS system using reversed phase LC, where enhanced analyte separation was possible by programming the mobile phase during elution, showed that it was possible to target and quantitate methotrexate and its major metabolite 7-hydroxy methotrexate in urine from human patients suffering from rheumatoid arthritis [87].…”
Section: Multiplexed Quantification From Sers Of Mixturesmentioning
confidence: 99%
“…On this premise, to realise the maximum benefits of SERS, there is a need to target known biomarkers identified a priori by other techniques, such as LC-MS or GC-MS, polymerase chain reaction (PCR), etc. As a case in point, Subaihi and coworkers used reversed-phase LC to separate therapeutic drugs in human urine followed by quantitative detection by SERS [28]. Furthermore, specific disease markers can be detected by SERS method, which has been extensively reported by Graham and Faulds and coworkers [23,29].…”
Section: Introductionmentioning
confidence: 99%
“…[16] As such, SE(R)RS analysis of samples in biological media with colloidal substrates has typically required pre-treatment steps to first remove proteins from the sample,w hich is inconvenient and time-consuming. [17] Alternatively,i ti sa lso possible to first aggregate the colloid with salt to form hot-spots before adding in the sample.H owever,t his narrows the window for SE-(R)RS analysis and adds to the irreproducibility of the measurements. [18] To test the potential of SPAs for SE(R)RS analysis in biological media, samples of adenine dissolved in 3.3 %a lbumin solution were used to provide as imple biologically-relevant test molecule in as olution whose protein content matched that of human serum.…”
Section: Angewandte Chemiementioning
confidence: 99%